An analysis of the adequacy of the library collection to the studio arts programs of the College of Fine Arts - Robles, Lissette R.; Lapuz, Elvira B. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The study focused on answering if the College of fine Arts Library collection is adequate in providing the information needs of the students under the Department of Studio Arts. Two evaluation schemes were utilized in the study: collection-centered and use-centered evaluation. A comparison against the existing PAARL standards was used as the collection-centered parameter. The amount of book collection under the college library's safe keeping was weighed against the 5,000 titles plus additional 5 titles per student book requirement. Review of book loans made for the past three years (2001-2003) served as the use-centered evaluation resources. Subject areas frequently borrowed during this period of time were analyzed.
An inventory of the existing book collection was used to identify the materials designated for each relevant fine art subject areas. Immediate findings showed that (a) seventy eight percent (78.18 percent) of the library's total book collection is intended for Fine Arts subjects, (b) only the subjects SFA 100, SFA 101, SFA 102 and SFA 103 are exclusively offered for Studio Arts students, (c) LC Subclasses for N such as Class NB (Sculpture) and Class ND (Painting) satisfies these subjects for Studio Arts and (d) a greater amount of titles on Painting are available compared to the titles on the subject area of Sculpture.
Employing the existing PAARL standards, the library was able to meet one hundred percent (100percent) of the required book holdings. This implied that there is an available 5,000 titles core collection and 3567 titles for the 712 presently enrolled students. The review on loans showed that greatly borrowed materials include the subject areas of 1) Visual Arts, 2) Painting, 3) Drawing and Design 4) Decorative Arts and 5) Photography.
In comparing the number of titles available against the number of materials borrowed for the past three years, the percentage for Sculpture (NB) and Painting (ND) exceeds the percentages of loans. This assumed under usability of materials can be attributed fewer users who utilize these items or the possibility that there are more materials available to be borrowed compared to the regular number of users. With this, it can be presupposed that until now even if the demands for materials on this subject area increase, there is relatively sufficient materials to cater to the patrons needs.
The study concluded that through this comparison against standards and its review of book loans illustrated that the college library's collection can be assumed adequate for the Studio Arts students information needs. The analysis recommends that a) the library should maintain its support for the FA required subjects, b) reviews of enrollment patterns and the curricula for each program, should be considered to recognize the fields that should be given attention, c) faculty should greatly be involved in the selection of materials to be included in the collection, and d) regular comparison against standards and constant checking of the statistics of usage of materials are helpful tools in reviewing the adequacy of the collection.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines -- College of Fine Arts. Library; Art libraries -- Collection development -- Philippines -- Quezon City